Agro-ecological and artisanal production markets: Sustainability and gentrification in Mexico City - Pasquier-Merino, Ayari G. (2024)
Agroecological and artisanal produce markets have multiplied as part of a broader process that promotes food citizenship oriented towards justice and sustainability. However, this phenomenon is immersed in the complexity of food systems and entails great heterogeneity. This article analyzes the relationship between these types of initiatives and the gentrification processes in some of the areas where they are established. The topic is approached from ethnographic material collected in the framework of a research project on agroecological production initiatives and artisanal transformation in Mexico City and on the citizens’ collectives that facilitate the commercialization of this production. The findings show that in certain areas of the city these markets shape a broader set of “alternative” food supply networks linked to gentrification processes and the findings identify some of the factors that affect the reproduction of social inequalities within the framework of these initiatives. At the same time, the study underscores the agency of the actors involved and documents their abilities to use these spaces through the growing demand for fresh, healthy, and locally-sourced food to advance their own ends in areas subject to gentrification.